Participation of Endosomes in Toll-Like Receptor 3 Transportation Pathway in Murine Astrocytes - Mielcarska, Matylda B.; Gregorczyk-Zboroch, Karolina P.; Szulc-Dąbrowska, Lidia; Bossowska-Nowicka, Magdalena; Wyżewski, Zbigniew; Cymerys, Joanna; Chodkowski, Marcin; Kiełbik, Paula; Godlewski, Michał M.; Gieryńska, Małgorzata; Toka, Felix N. (Frontiers in Cellular Neuroscience, 2020)
TLR3 provides immediate type I IFN response following entry of stimulatory PAMPs into the CNS, as it is in HSV infection. The receptor plays a vital role in astrocytes, contributing to rapid infection sensing and suppression of viral replication, precluding the spread of virus beyond neurons. The route of TLR3 mobilization culminating in the receptor activation remains unexplained. In this research, we investigated the involvement of various types of endosomes in the regulation of the TLR3 mobility in C8-D1A murine astrocyte cell line. TLR3 was transported rapidly to early EEA1-positive endosomes as well as LAMP1-lysosomes following stimulation with the poly(I:C). Later, TLR3 largely associated with late Rab7-positive endosomes. Twenty-four hours after stimulation, TLR3 co-localized with LAMP1 abundantly in lysosomes of astrocytes. TLR3 interacted with poly(I:C) intracellularly from 1 min to 8 h following cell stimulation. We detected TLR3 on the surface of astrocytes indicating constitutive expression, which increased after poly(I:C) stimulation. Our findings contribute to the understanding of cellular modulation of TLR3 trafficking. Detailed analysis of the TLR3 transportation pathway is an important component in disclosing the fate of the receptor in HSV-infected CNS and may help in the search for rationale therapeutics to control the replication of neuropathic viruses.